PENGARUH DIVERSIFIKASI OPERASIONAL TERHADAP STRUKTUR MODAL DENGAN KEPEMILIKAN PEMERINTAH SEBAGAI VARIABEL MODERASI (Studi pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2012) - Rahayu, Indu Prasetya Ning; Rohman, Abdul (Diponegoro Journal of Accounting, 2014)
The purposes of this research are (1) to examine the influences of operational diversification on capital structure of a firm, (2) to examine the influences of goverment ownership based on the relation between operational diversification and capital structure. Diversification level is measurd by Jacquemin – Berry entrophy index, while capital structure is measure by book leverage, market leverage and long – term market leverage. Goverment ownership as moderate variabel is measured with dummy variabel. As control variabel, this reasearch used return on Assets, non - current aset ratio, non-debt tax shield, Tobin’s Q, biggest stock ratio, board ratio, size and age of firm.Population of this reasearch consists of all listed non – financial firms in Indonesia Stock Exchange in year 2010 – 2012. The sampling method used in this research in purposive sampling. After doing sampling and processing datas, 147 firms randomly selected. This research use panel data regression to examine the hypothesis.The empirical evidence show that related diversification significant positive influence on capital structure and unrelated diversification significant negative on capital structure. The result of moderate variabel show that debilitation of goverment ownership negative relation between related diversification and capital structure. Meanwhile, debilitation of goverment ownership positive relation between unrelated diversification and capital structure.